Self Awareness and the Effective Counsellor: A Framework for Assessment - Uhlemann, Max R.; Jordan, David (Canadian Journal of Counselling and Psychotherapy, 2012)
Jevne (1981) found self awareness to be considered first among competency areas necessary for training an effective counsellor. In response to this finding, a view of the concept is presented which could serve as the basis for systematic assessment of the competency area. A two-dimensional matrix composed of content and process dimensions is elaborated to examine self awareness. The content dimension is based on components of the concept presented by Jevne. To clarify the integration of the content and process dimensions of the matrix, examples of self aware and non-self aware expressions are presented. Other counselling professionals are encouraged to present their views of self awareness so the competency area may be clarified, and implemented in counsellor training.